2023
DOI: 10.1111/faf.12779
|View full text |Cite
|
Sign up to set email alerts
|

Pacific cod in the Anthropocene: An early life history perspective under changing thermal habitats

Abstract: The rapid decline in Pacific cod (Gadus macrocephalus, Gadidae) biomass following multiple Gulf of Alaska marine heatwaves (2014–2016 and 2019) may be one of the most dramatic documented changes in a sustainably managed marine fishery. As such, fisheries managers are exploring new recruitment paradigms for Pacific cod under novel environmental conditions. In this review, we address the challenges of managing and forecasting Pacific cod populations in the Eastern Pacific where thermal habitats for early life st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 119 publications
0
3
0
Order By: Relevance
“…In the GOA ecosystem, MHW events are likely to become longer and more frequent due to anthropogenic climate change 1 , and Pacific cod will need to either adapt to these novel conditions or migrate to new environments with more suitable thermal habitat 71 , 72 . Since the 1990s, southern populations of Pacific cod in the Pacific Northwest and British Columbia have experienced steep declines 45 , and similar patterns in the GOA population may suggest that a phenomenon analogous to winter mortality could become more common with long-term and acute warming 73 . During the MHWs, we observed patterns in juvenile Pacific cod size, diet composition, and growth that were distinct from other years in our analysis, suggesting broad similarities across years associated with MHWs.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In the GOA ecosystem, MHW events are likely to become longer and more frequent due to anthropogenic climate change 1 , and Pacific cod will need to either adapt to these novel conditions or migrate to new environments with more suitable thermal habitat 71 , 72 . Since the 1990s, southern populations of Pacific cod in the Pacific Northwest and British Columbia have experienced steep declines 45 , and similar patterns in the GOA population may suggest that a phenomenon analogous to winter mortality could become more common with long-term and acute warming 73 . During the MHWs, we observed patterns in juvenile Pacific cod size, diet composition, and growth that were distinct from other years in our analysis, suggesting broad similarities across years associated with MHWs.…”
Section: Discussionmentioning
confidence: 98%
“…Dramatic declines of Pacific cod larval and age-0 juvenile abundances occurred almost immediately following the onset of MHW conditions, likely due to reduced hatch success 44 and potential mismatches in prey resources available to first-feeding larvae 23 . Follow-up studies found additional demographic changes in age-0 cohorts during MHWs, including a nearly 3-week shift to earlier hatch dates in the spring 19 , which contributed to predominantly larger and older juveniles entering coastal habitats in early summer 45 . During the MHWs, relatively large body size and low abundance of juvenile Pacific cod were observed post-settlement in coastal habitats across the GOA 46 .…”
Section: Introductionmentioning
confidence: 99%
“…The ecological changes during and after this period have primarily been attributed to prolonged, elevated ocean temperatures, yet the consideration of O 2 and pH may also explain ecosystem changes not yet identified or understood. The warm ocean temperatures are suggested to have affected Pacific cod by exceeding optimal thermal thresholds of cod egg and larval survival (Laurel et al, 2023), and increasing metabolic rates, resulting in increased O 2 demand and consumption rates in a reduced prey environment (Barbeaux et al, 2020). However, the cod population has not yet rebounded, despite the return of pre-marine heatwave ocean temperatures and prey abundance, suggesting missing pieces to the narrative.…”
Section: What Does This Mean For the Gulf Of Alaska Marine Ecosystem?mentioning
confidence: 99%